Liver transplantation: expectation with MELD score for liver allocation in Brazil - Teixeira,Andreza Correa (2006)
Liver transplantation represents the most effective therapy for patients suffering from chronic end-stage liver disease. Until very recently, in Brazil, liver allocation was based on the Child-Turcotte-Pugh score and the waiting list followed a chronological criterion. In February 2002 the Model for End-stage Liver Disease (MELD) score was adopted for the allocation of donor livers in the US. After that change, an increased number of patients with more severe liver disease was observed, although there was no difference in 1-year patient and graft survival. A reduction in waiting-list mortality was also observed. In Brazil, the MELD score was adopted on May 31st, 2006. Good results are expected regarding the new criterion for allocation.